Relevance of QuantiFERON-TB Gold Plus and Heparin-Binding Hemagglutinin Interferon-γ Release Assays for Monitoring of Pulmonary Tuberculosis Clearance: A Multicentered Study - Chedid, Carole; Kokhreidze, Eka; Tukvadze, Nestani; Banu, Sayera; Uddin, Mohammad Khaja Mafij; Biswas, Samanta; Russomando, Graciela; Acosta, Chyntia Carolina Díaz; Arenas, Rossana; Ranaivomanana, Paulo PR.; Razafimahatratra, Crisca; Herindrainy, Perlinot; et al. (Frontiers in Immunology, 2021)
Tuberculosis (TB) is a leading infectious cause of death. To improve treatment efficacy, quicker monitoring methods are needed. The objective of this study was to monitor the response to a heparin-binding hemagglutinin (HBHA) interferon-γ (IFN-y) release assay (IGRA) and QuantiFERON-TB Gold Plus (QFT-P), and to analyze plasma IFN-y levels according to sputum culture conversion and immune cell counts during treatment. This multicentered cohort study was based in Bangladesh, Georgia, Lebanon, Madagascar, and Paraguay. Adult, non-immunocompromised patients with culture-confirmed pulmonary TB were included. Patients were followed up at baseline (T0), after two months of treatment (T1), and at the end of therapy (T2). Clinical data and blood samples were collected at each timepoint. Whole blood samples were stimulated with QFT-P antigens or recombinant methylated Mycobacterium tuberculosis HBHA (produced in Mycobacterium smegmatis; rmsHBHA). Plasma IFN-y levels were then assessed by ELISA. Between December 2017 and September 2020, 132 participants completed treatment, including 28 (21.2%) drug-resistant patients. rmsHBHA IFN-y increased significantly throughout treatment (0.086 IU/mL at T0 vs. 1.03 IU/mL at T2, p<0.001) while QFT-P IFN-y remained constant (TB1: 0.53 IU/mL at T0 vs. 0.63 IU/mL at T2, p=0.13). Patients with low lymphocyte percentages (<14%) or high neutrophil percentages (>79%) at baseline had significantly lower IFN-y responses to QFT-P and rmsHBHA at T0 and T1. In a small group of slow converters (patients with positive cultures at T1; n=16), we observed a consistent clinical pattern at baseline (high neutrophil percentages, low lymphocyte percentages and BMI, low TB1, TB2, and MIT IFN-y responses) and low rmsHBHA IFN-y at T1 and T2. However, the accuracy of the QFT-P and rmsHBHA IGRAs compared to culture throughout treatment was low (40% and 65% respectively). Combining both tests improved their sensitivity and accuracy (70-80%) but not their specificity (< 30%). We showed that QFT-P and rmsHBHA IFN-y responses were associated with rates of sputum culture conversion. Our results support a growing body of evidence suggesting that rmsHBHA IFN-y discriminates between the different stages of TB, from active disease to controlled infection. However, further work is needed to confirm the specificity of QFT-P and rmsHBHA IGRAs for treatment monitoring.